Characterization of a Highly Thermostable Alkaline Phosphatase from the Euryarchaeon Pyrococcus abyssi - Zappa, Sébastien (American Society for Microbiology, 2001)
This work reports the first isolation and characterization of an alkaline phosphatase (AP) from a hyperthermophilic archaeon. An AP gene from Pyrococcus abyssi, a euryarchaeon isolated from a deep-sea hydrothermal vent, was cloned and the enzyme expressed in Escherichia coli. Analysis of the sequence showed conservation of the active site and structural elements of the E. coli AP. The recombinant AP was purified and characterized. Monomeric and homodimeric active forms were detected, with a monomer molecular mass of 54 kDa. Apparent optimum pH and temperature were estimated at 11.0 and 70°C, respectively. Thus far, P. abyssi AP has been demonstrated to be the most thermostable AP, with half-lives at 100 and 105°C of 18 and 5 h, respectively. Enzyme activity was found to be dependent on divalent cations: metal ion chelators inhibited activity, whereas the addition of exogenous Mg(II), Zn(II), and Co(II) increased activity. The enzyme was inhibited by inorganic phosphate, but not by molybdate and vanadate. Strong inhibitory effects were observed in the presence of thiol-reducing agents, although cysteine residues of the P. abyssi AP were not found to be incorporated within intra- or interchain disulfide bonds. In addition, P. abyssi AP was demonstrated to dephosphorylate linear DNA fragments with dephosphorylation efficiencies of 93.8 and 84.1% with regard to cohesive and blunt ends, respectively.